Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Aparatur Peradilan Dengan Motivasi Kerja sebagai Variabel Intervening pada Peradilan Agama Se-Sumatera Barat - Hidayat, Rifka; Almasdi, Almasdi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
In West Sumatra Province, judicial power within the religious judiciary is carried out by the Padang High Court of Religion and 18 work units of the Religious Courts throughout West Sumatra. Court service is an activity in the context of fulfilling service needs for the community, specifically justice seekers based on the laws and regulations and the principles of public service. As an institution with the principles of public service, the judiciary must continuously improve organizational performance. Improved organizational performance will be achieved by increasing the performance of the apparatus on duty in each work unit within the judiciary. Factors that affect the performance of the judicial apparatus can be internal and external factors. This study aims to reveal the influence of organizational culture and job satisfaction on the performance of the judicial apparatus with work motivation as an intervening variable in the Religious Courts of West Sumatra. The subject of the study was the apparatus of the Religious Courts of West Sumatra as many as 106 people were determined using the proportionate stratified random sampling technique. This type of research is quantitative research. Data collection techniques using a questionnaire with a Likert scale model of 5 alternative answers. Data analysis was performed using SEM (Structural Equation Modeling) analysis which was operated based on Partial Least Square (PLS) with three independent variables and one dependent variable. This study found that organizational culture had a positive and significant effect on the performance of the judicial apparatus, while job satisfaction had no effect on the performance of the judicial apparatus in the Religious Courts of West Sumatra, however, organizational culture and job satisfaction had a positive and significant effect on the work motivation of the judicial apparatus in the Religious Courts of West Sumatra. Meanwhile, work motivation does not mediate the relationship between organizational culture and job satisfaction with the performance of the judicial apparatus in the Religious Courts throughout West Sumatra.